Flexible Bronchoscopy in Children: The Marmara University Division of Pediatric Pulmonology Experience - Almala Pınar Ergenekon; Ecenur Şahin; Cansu Yılmaz Yeğit; Mürüvvet Yanaz; Aynur Gulieva; Mine Kalyoncu; Merve Selçuk; Ela Erdem Eralp; Yasemin Gökdemir; Bülent Taner Karadağ (Çocuk Dergisi)
Objective: The use of flexible bronchoscopy for diagnosis and/or treatment in pediatric patients has increased considerably in recent years with new indication areas. The aim of the current study is to present our experience with 732 flexible bronchoscopy procedures performed over 5 years in our Pediatric Pulmonology Clinic. Materials and Method: The study involves children under the age of 18 years who’ve undergone flexible bronchoscopy. Demographic characteristics, flexible bronchoscopy indications and findings, complications, and bronchoalveolar lavage results have been recorded. Results: Patients’ median age is 5 years (range from 2-10 years). The most common indication of FB is recurrent lower respiratory tract infection (29.6%), followed by chronic cough (16.4%). Of the patients 49 (6.7%) had an immunodeficiency and 42 (5.7%) had a malignancy. The bronchoscopic evaluations revealed normal airway anatomies in 250 (34.2%) patients. At least one pathological finding was detected in 482 (65.8%) patients. The most common findings were increased airway secretions in 268 (36.6%) patients and bronchomalacia in 66 (9%) patients. Microbiological growth presented for at least one microorganism in 111 (20.8%) patients. Haemophilus infleunzae was the most frequently identified bacteria. No major complications were observed. Conclusion: Flexible bronchoscopy is very valuable for patients with recurrent lower respiratory tract infections in terms of bronchoalveolar lavage culture results and appropriate antibiotic therapy. Flexible bronchoscopy is essential for detecting laryngomalacia or secondary airway lesions in patients with stridor and is an important tool for definitively diagnosing bronchomalacia in patients with persistent wheezing and chronic cough.